Foreign Direct Investment and Welfare: Is Sub-Saharan Africa Different? - Ranjkeshan,Aida (2021)
Foreign Direct Investment (FDI) is often considered to be favorable to long-run economic growth and has in recent years been promoted as a poverty-reducing tool. Although FDI to developing countries has increased rapidly in recent decades, Sub-Saharan Africa (SSA) has been unsuccessful in attracting large inflows of FDI. This study assesses the effect FDI has had on poverty and human development in Sub-Saharan Africa. The paper also explores what the determinants of FDI are in SSA. The study employs Fixed Effects and General Method of Moments (GMM) methods to empirically analyze the effects of FDI. The results found indicate: i) a weak relationship between FDI and human development, ii) lower levels of corruption and better infrastructure having a positive effect on human development, and that iii) the FDI inflows to SSA are of resource- and market-seeking nature. These results imply that FDI alone is not a solution for either poverty or human development in the long run.
Keywords: Sub-Saharan Africa; Foreign Direct Investment; Poverty; Human Development; HDI; Fixed Effects; General Method of Moments